Figure 6 from: Dehon M, Engel MS, Gérard M, Aytekin AM, Ghisbain G, Williams PH, Rasmont P, Michez D (2019) Morphometric analysis of fossil bumble bees (Hymenoptera, Apidae, Bombini) reveals their taxonomic affinities. ZooKeys 891: 71-118. https://doi.org/10.3897/zookeys.891.36027 - Dehon, Manuel; Engel, Michael S.; Gérard, Maxence; Aytekin, A. Murat; Ghisbain, Guillaume; Williams, Paul H.; Rasmont, Pierre; Michez, Denis (Zenodo, 2019)
Figure 6 Hypothesis of bumble bee evolution according to the branching dates of Hines (2008) alone with the subgeneric system of Williams et al. (2008). Fossils are mapped onto the clade according to our hypotheses based on our wing morphometry/shape results. Geometric morphometric analyses should be considered as a heuristic tool given the absence of other forms of pertinent data (e.g., absence of information on mandibular form, pretarsal structure, genitalic characters, etc.). A = Alpinobombus. B = Bombus s.str. LF = clade with mostly long-faced species. P = Pyrobombus. SF = clade with mostly short-faced species.